INTERPERSONAL MEANING ON TEACHER TALK: A FUNCTIONAL GRAMMAR APPROACH - Santi Jaya Hutabarat; Willem Saragih; Masitowarni Siregar (Universitas Negeri Medan, 2019)
This study was aimed to find out the interpersonal meaning realization on teacher talk and to describe the underlying reason of its realization. The research was conducted by using descriptive qualitative. The data were the talks of English teacher at SMA SwastaTeladan Medan. The data were analyzed based on interpersonal meaning analysis of Systemic Functional Grammar which introduced by M.A.K Halliday. The findings of this study showed that 226 of 248 clauses were identified as mood, 98 of 248 clauses expressed modality and 22 of 248 of clauses were identified as minor clause.Further, the distribution of mood types showed that there were three types of mood realized on teacher talk. They were declarative mood (58 %), interrogative mood (17 %), and imperative mood (16 %). Moreover, the distribution of modality showed that 27 of 98 clauses (27 %) were used modal adverb which expressed median value of probability, 16 % of clauses were identified as high obligation (have to, must), then followed by 13 % of clauses were identified as median obligation through the use modal finite of should and need to.